2012
DOI: 10.1149/2.021204jss
|View full text |Cite
|
Sign up to set email alerts
|

Contact Behavior and Chemical Mechanical Polishing (CMP) Performance of Hole-Type Polishing Pad

Abstract: A polishing pad plays an essential role in determining the chemical mechanical planarization (CMP) performance such as removal rate, planarization, and defectivity. Further, it is important for the polishing pad to maintain good CMP performance throughout its lifespan. In order to achieve high performance and durability, a hole-type pad was suggested as an alternative to the conventionally used pore-type pad. In this study, the effect of the hole density on the CMP performance was examined for a hole-type pad.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This difference can explain the above result, that is, the lower compressibility of IC1000 causes better planarity as in the case of ILD planarization [19][20][21] and also causes a lower RR because of the less contact of the pad with the wafer due to the lower flexibility, which cannot compensate for the pad surface waviness. 25) However, as will be discussed later, the mechanism of local planarization such as STI or Cu damascene CMP must be different from that of global planarization such as that of ILD CMP, and other factors are considered to dominate the mechanism. One possible factor is the temperature during polishing.…”
Section: Resultsmentioning
confidence: 99%
“…This difference can explain the above result, that is, the lower compressibility of IC1000 causes better planarity as in the case of ILD planarization [19][20][21] and also causes a lower RR because of the less contact of the pad with the wafer due to the lower flexibility, which cannot compensate for the pad surface waviness. 25) However, as will be discussed later, the mechanism of local planarization such as STI or Cu damascene CMP must be different from that of global planarization such as that of ILD CMP, and other factors are considered to dominate the mechanism. One possible factor is the temperature during polishing.…”
Section: Resultsmentioning
confidence: 99%
“…Some scholars have developed parametric analyses and even statistical models for microscale contact states [3]. Kim et al [4] found that increasing the pore density increased the contact rate and thus reduced the number of scratches. Lee et al [5] and Khanna et al [6] described microscale contact states through parameters such as polishing pad height distribution and deflection angle, smoothness, and gap coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…4,8,9 In particular, the CMP pad plays a key role in CMP performance because it is in direct contact with the wafer during polishing. 10,11 Mechanical abrasion is supplied by the mechanical friction between pad asperities, abrasive, and the chucked wafer. Therefore, the roughness of the CMP pad surface and its recovery from deformation are crucial.…”
mentioning
confidence: 99%